In Situ Generated Gold Nanoparticle Hybrid Polymersomes for Water‐Soluble Chemotherapeutics: Inhibited Leakage and pH‐Responsive Intracellular Release. (23rd March 2017) - Fu, Jun; Liang, Lina; Qiu, Liyan
Abstract : Drug leakage in blood circulation is generally a serious concern to polymersomes when loading water‐soluble chemotherapeutics. If packing density of polymersome membrane is strengthened, premature drug release will be inhibited. Therefore, synthesis of a series of amphiphilic polyphosphazenes (PNPs) with 2‐diethylaminoethyl 4‐aminobenzoate (DEAB) as hydrophobic side groups and amino‐terminal poly(ethylene glycol) (NH2 ‐PEG2000 ) as hydrophilic chains is presented. By controlling the ratio of DEAB to NH2 ‐PEG2000, the optimal PNP‐3 is screened to ensure polymersome formation and high loading of doxorubicin hydrochloride (DOX·HCl). In situ generation method is initially employed to introduce gold nanoparticles (AuNPs) into vesicles' lamella, which can homogeneously distribute among DEAB sides via coordination interaction and act as inorganic cross‐linkers to aggregate polymer chains. Drug leakage of resultant AuNP hybrid PNP‐3 polymersome (IAuPNP‐3) at pH 7.4 is effectively alleviated and the systemic circulation time of DOX·HCl in mice is obviously prolonged. Besides, pH‐responsive drug release, due to the protonation of tertiary amine in DEAB, contributes to fast intracellular action. Based on the cooperation of these functions, DOX·HCl‐loaded IAuPNP‐3 finally achieves the highest in vivo antitumor efficacy compared with free DOX·HCl, drug‐loaded PNP, or EAuPNP prepared by prepreparation AuNPs method. Abstract : Gold nanoparticle hybrid polymersomes based on amphiphilic pH‐sensitive polyphosphazenes (IAuPNP‐3) are constructed by in situ generation method to inhibit the leakage of water‐soluble doxorubicin hydrochloride (DOX·HCl) during circulation due to strengthened packing density of polymersome membrane, as well as to facilitate pH‐responsive intracellular drug release. Consequently, DOX·HCl‐loaded IAuPNP‐3 significantly improves in vivo antitumor efficacy.